Mechanical and Thermal Properties of Polypropylene Reinforced by Calcined and Uncalcined Zeolite - Bukit, Nurdin (UI Scholars Hub, 2012)
This study was carried out to compare mechanical and thermal properties of polypropylene (PP) reinforced with uncalcined and calcined zeolites. The PP samples were reinforced with zeolites at various quantities of 2, 4, and 6 (wt %). The comparison of the two types of zeolite was based on mechanical properties, including tensile strength, elongation at break, and Young’s modulus, and thermal characteristics analyzed using DSC, and DTA/TGA technique. The results obtained clearly revealed that both zeolites were able to significantly increase tensile strength and Young’s modulus of the samples, with calcined zeolite was found to work better. Addition of calcined zeolite was found to result in increased fracture elongation of the samples reinforced with up to 4 wt% zeolite but decreased sharply for the sample reinforced with 6 wt% zeolite, while for the samples reinforced with uncalcined zeolite, no consistent trend was observed. Thermal analyses demonstrated that the samples reinforced with calcined zeolite are more resistant to thermal treatment than those reinforced with uncalcined zeolite, as indicated by their higher decomposition temperature. DSC analysis revealed that there was no significant difference of the melting points of the samples was observed, but the effect of the quantity of zeolite on enthalphy was quite evident, in which the enthalpies of the samples reinforced with calcined zeolites were relatively lower than those of the samples reinforced with uncalcined zeolites.